Frailty and risk of adverse outcomes among community-dwelling older adults in China: a comparison of four different frailty scales - Qin, Fei; Guo, Yanfei; Ruan, Ye; Huang, Zhezhou; Sun, Shuangyuan; Gao, Shuna; Ye, Jinghong; Wu, Fan (Frontiers in Public Health, 2023)
Background: Data on which frailty scales are most suitable for estimating risk in Chinese community populations remain limited. Herein we identified and compared the utility of four validated frailty scales in identifying frailty, together with their ability to predict adverse outcomes in a large population-based cohort of Chinese older adults. Methods: A total of 5402 subjects (mean age 66.3 ± 9.6 years, 46.6% male) from the WHO Study on global AGEing and adult health (SAGE) in Shanghai were studied. Frailty was measured using a 35-item frailty index (FI), the frailty phenotype (FP), FRAIL, and Tilburg Frailty Indicator (TFI). Multivariate logistic regression models were performed to evaluate the independent association between frailty and outcomes including 4-year disability, hospitalization, and 4- and 7-year all-cause mortality. The accuracy for predicting these outcomes was determined by evaluating the area under the curve (AUC). Prevalence of frailty, sensitivity, and specificity were calculated using our proposed cut-off points and other different values. Results: Prevalence of frailty ranged from 4.2% (FRAIL) to 16.9% (FI). FI, FRAIL and TFI were comparably associated with 4-year hospitalization, and 4- and 7-year mortality (adjusted odds ratios [aORs] 1.44-1.69, 1.91-2.22 and 1.85-2.88, respectively). FRAIL conferred the greatest risk of 4-year disability, followed by FI and TFI (aOR 5.55, 3.50 and 1.91, respectively). FP only independently predicted 4- and 7-year mortality (aOR 1.57 and 2.21, respectively). AUC comparisons showed that FI, followed by TFI and FRAIL, exhibited acceptable predictive accuracy for 4-year disability, 4- and 7-year mortality (AUCs 0.76-0.78, 0.71-0.71, 0.65-0.72, respectively), whereas all scales poorly predicted 4-year hospitalization (AUCs 0.53-0.57). For each scale, while specificity estimates (85.3-97.3%) were high and similar across all outcomes, their sensitivity estimates (6.3-56.8%) were not sufficient yet. Prevalence of frailty, sensitivity, and specificity varied considerably when different cut-offs were used. Conclusions: Frailty defined using FI, FP, FRAIL, and TFI was independently associated with 4-year disability (except FP), hospitalization (except FP), and 4- and 7-year mortality. However, these four scales exhibited different properties in estimating risk; FI performed best, while TFI and FRAIL were additionally useful, the latter perhaps being more applicable to Chinese community-dwelling older adults.